PELAKSANAAN PENEGAKAN HUKUM OLEH KEPOLISIAN DAERAH BALI DALAM TINDAK PIDANA FIDUSIA DI WILAYAH HUKUM POLDA BALI - Putra, I Wayan Partama; Indradewi, Anak Agung Sagung Ngurah; Pramesti, I Putu Eka Yoga (The Juris, 2023)
The clause 4 of Law Number 42 of 1999 concerning Fiduciary Guarantees confirms that Fiduciary Guarantees are a follow-up agreement to a principal agreement which creates an obligation for the parties to fulfill an agreement achievement. The failure to achieve the agreement achievement from the debtor makes the person concerned have to face a legal process, which begins with the investigation from Police. Based on the background of the problems above, several problems can be formulated, including what is the role of law enforcers for Bali Regional Police in fiduciary crimes in the Legal Area of the Bali Regional Police? And what are the obstacles that faced by the Bali Regional Police in enforcing the law on fiduciary crimes in the Bali Regional Police Legal Area? The research method used is an empirical research method by examining the practice of implementing Law Number 42 of 1999 concerning Fiduciary Guarantees with data collection techniques through document studies and through interviews with investigators from the Special Criminal Investigation Directorate of the Bali Regional Police. The results of the study show the following conclusions: first, the role played by the investigator is the role of prevention (preventive) and repression (repressive) against the perpetrators of crime. Second, there are internal and external inhibiting factors in the implementation of law enforcement on fiduciary crimes.